2017
DOI: 10.5897/ajmr2017.8526
|View full text |Cite
|
Sign up to set email alerts
|

Atypical manifestation in infection by methicillin-resistant Staphylococcus aureus carrier SCCmec IV and Panton-Valentine Leukocidin-producer in experimental sepsis model

Abstract: Staphylococcus aureus is considered an infectious agent of great clinical importance, responsible for many different types of infection. Strains of methicillin-resistant Staphylococcus aureus (MRSA), Panton-Valentine leukocidin producers, are considered more invasive, presenting clinical sequelae related to abscesses and infection in skin and soft tissues. The use of invasive techniques in hospital environment, such as the introduction of intravascular catheter in immunocompromised patients, has contributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As a result of the inflammatory response, systemic infections may evolve to septic shock (Souza and Fontanetti 2006;Klevens et al 2007;Boles and Horswill 2008). Nevertheless, the most common infections occur in soft tissues (Lowy 1998;Kim et al 2014;Silva-Santana et al 2016;Silva-Santana et al 2017) presenting pathological characteristics such as purulent lesions and abscesses caused by infiltration of neutrophils in contaminated sites (Cheng et al 2009;Stearns-Kurosawa et al 2011;Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result of the inflammatory response, systemic infections may evolve to septic shock (Souza and Fontanetti 2006;Klevens et al 2007;Boles and Horswill 2008). Nevertheless, the most common infections occur in soft tissues (Lowy 1998;Kim et al 2014;Silva-Santana et al 2016;Silva-Santana et al 2017) presenting pathological characteristics such as purulent lesions and abscesses caused by infiltration of neutrophils in contaminated sites (Cheng et al 2009;Stearns-Kurosawa et al 2011;Kim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that 89% of S. aureus isolates is resistant to b-lactam antibiotics (methicillinresistant S. aureus, MRSA) (Amalaradjou and Venkitanarayanan 2014;Santana et al 2015). Nowadays, the recommended therapy includes vancomycin, linezolid and daptomycin for the treatment of infections caused by MRSA (Arbeit et al 2004;Liu et al 2011;Kim et al 2014;Silva-Santana et al 2016;Silva-Santana et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations